2020
DOI: 10.1002/mbo3.1036
|View full text |Cite
|
Sign up to set email alerts
|

Porcine deltacoronavirus infection alters bacterial communities in the colon and feces of neonatal piglets

Abstract: Porcine deltacoronavirus (PDCoV) is a novel enteropathogenic coronavirus that causes watery diarrhea in piglets. Little is known regarding the alteration of the gut microbiota in PDCoV‐induced diarrhea piglets. In this study, 5‐day‐old piglets were experimentally infected with PDCoV strain CH‐01, and all piglets developed typical clinical disease, characterized by acute and severe watery diarrhea. Histologic lesions were limited to the villous epithelium of the duodenum and ileum. Gut microbiota pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Surprisingly, few studies have addressed the impact of coronavirus infection on the gut microbiota and most of them focused on chicken and pig models (induction of microbial imbalance). 65 69 Recent studies have reported the impact of a SARS-CoV-2 infection on the gut microbiota in humans. 52 , 70 – 73 Briefly, SARS-CoV-2 infection lowered the abundance of butyrate producers such as several genera from the Ruminococcaceae and Lachnospiraceae ( Roseburia ) families.…”
Section: Impact Of Viral Respiratory Tract Infections On the Gut Micrmentioning
confidence: 99%
“…Surprisingly, few studies have addressed the impact of coronavirus infection on the gut microbiota and most of them focused on chicken and pig models (induction of microbial imbalance). 65 69 Recent studies have reported the impact of a SARS-CoV-2 infection on the gut microbiota in humans. 52 , 70 – 73 Briefly, SARS-CoV-2 infection lowered the abundance of butyrate producers such as several genera from the Ruminococcaceae and Lachnospiraceae ( Roseburia ) families.…”
Section: Impact Of Viral Respiratory Tract Infections On the Gut Micrmentioning
confidence: 99%
“…Compared to RV and NoV infections alone, EPEC and EAEC co-infections aggravate the frequency of diarrhea and vomiting [13]. Co-infections lead to altered intestinal flora abundance, decreased intestinal microbial diversity, and increased intestinal flora disorders [14,15], such as accomplished with a higher abundance of Clostridiaceae and Streptococcaceae within the gut, the microbiota can interact directly with epithelial cells, leading to a series of events in the process of inflammatory [13]. In contrast, Sabrina J. Moyo et al analyzed stool samples from 723 children with diarrhea in Tanzania and found that co-infections frequently occur in diarrhea, but that the pathogenicity of one pathogen is sometimes enhanced by co-infection and diminished by others, with no effect of co-infection on the severity of diarrhea [16].…”
Section: Introductionmentioning
confidence: 99%
“…Age is a noted factor in CoV pathology including with COVID-19 [55,56]. From this and other published studies there appears to be a window of 2-6 days in ovo, followed by days 11-24 post hatch in which poults are more susceptible to detectable infection [25,38,57]. Further infection studies with varied ages are needed to assess the ages in which chicks and poults are most susceptible to PDCoV infection.…”
Section: Discussionmentioning
confidence: 86%